Simultaneous adsorption of phosphate and tetracycline by calcium modified corn stover biochar: Performance and mechanism - Zhuo, Sheng-Nan; Dai, Tian-Chi; Ren, Hong-Yu; Liu, Bing-Feng (Bioresource technology, 2022)
•A calcium modified biochar was used to simultaneously adsorb phosphate and TC.•The phosphate adsorption relies on the chemical precipitation and ligand exchange.•Hydrogen bonding and π-π interactions are the main adsorption mechanism of TC. It is important to solve the problems of biomass treatment and combined contaminants removal in environmental remediation. In this study, a calcium (Ca) modified biochar (CaBC800) was fabricated using corn stover (CS) as a raw material to remove phosphate and tetracycline (TC). The experimental results indicate that CaBC800 can adsorb both inorganic phosphate and organic TC. The entire adsorption process corresponds to pseudo-second-order kinetics and Langmuir adsorption isotherm. The maximum adsorption capacities of phosphate and TC were 33.944 and 33.534 mg/g, respectively. The phosphate adsorption was demonstrated to mainly depend on the chemical precipitation by Ca2+ and ligand exchange by hydroxyl groups from CaBC800. Meanwhile, hydrogen bonding from oxygen functional groups and π-π interactions from aromatic rings are the main adsorption mechanisms of TC. This study provides a new adsorbent to efficiently remove phosphate and TC, and the simultaneous adsorption indicates the application potential of CaBC800 in wastewater remediation.